Goiânia, a metrópole periférica: fantasmagoria, experiências e viveres urbanos – Real Conquista e Jardins Madri - Soares, Rodrigo de Oliveira (2015)
In XXI century, Goiânia established itself as a metropolis in the brazilian backlands, even on modern discourses trails. The capital of Goiás has established itself as a urban phantasmagoria to become a commodity under control of real state capital and so, designed as an incomplete metropolis In this research we try to peer how this process created ways of living in the city and how these differences and how they solidified in its suburbs. Our case study was developed in the Southwestern region where, for the poorest, the suburbs is the only way to belong to the city and for the more affluent groups it's a way to get away from the city caos. By focusing our research on popular nesting Real Conquista and luxury horizontal condomonium called Jardins Madri, we conclude that they were born of a ghostly project of modernity wich Goiânia is and expression. With the contributions of historical materialism of Walter Benjamin, his readers and interpreters, we seek to historicizing the dynamic metropolization of Goiânia and buil a critical reading of this process. Seek, from the perspective monadological not to issue a closed story or another document of barbarism, but show real scenarios to help you understand how goianiense metropolis was formed and deployed in the XXI century.